The effects of early feeding with different pre-starter diets on growth performance, morphological development and microorganism content of the small intestine of broiler chicks - Bedirhan Celik, A; Sarica, Ş; Suicmez, M (Journal of the Hellenic Veterinary Medical Society, 2024)
The present study was conducted to compare the effects of feeding 2 different pre-starter diets to broiler chicks at 2 different times on growth performance, slaughtering parameters, morphological development of the small intestine segments and the microorganism content of the ileum of broilers. A total of 600 day-old Ross 308 male broiler chicks were randomly distributed into 5 treatment groups with 5 replicates of 24 chicks each. The experimental treatments included: SD10: broiler chicks were fed a corn-soybean meal-based starter diet for 0-10 days; 1PSD5: chicks were fed a first pre-starter diet based on corn-soybean meal for 0-5 days, afterwards they were fed a starter diet based on corn-soybean meal for 5-10 days; 1PSD10: chicks were fed the first pre-starter diet for 0-10 days; 2PSD5: chicks were fed a second pre-starter diet based on rice-soybean meal for 0-5 days, afterwards they were fed a starter diet based on corn-soybean meal for 5-10 days; 2PSD10: chicks were fed the second pre-starter diet for 0-10 days. Broilers were fed a basal diet based on corn and soybean meal until the end of the experimental period. The 1PSD5, 1PSD10, 2PSD5 and 2PSD10 treatments significantly increased final body weight (BW) and BW gain, decreased feed intake (FI) and improved feed conversion ratio (FCR) of broilers from 0 to 42 day compared to the SD10 treatment. The lowest FI and the best FCR of broilers during the period of 0 to 42 day were obtained by the 2PSD5 treatment. The 1PSD5, 1PSD10, 2PSD5 and 2PSD10 treatments significantly enhanced the hot- and cold-carcass yields and villus heights (VHs) and decreased crypt depths of small intestine segments of broilers on day 42. However, the experimental treatments did not significantly affect the the E.coli and Lactobacillus contents of ileum of broilers on day 42. In conclusion, feeding of chicks with the pre-starter diet based on rice-soybean meal supplemented with enzyme complex and synbiotic for 0-5 days was a more effective treatment in terms of performance especially FI and FCR, carcass yields and VHs of small intestine segments of broilers.